A Comparative Study of the Complexity of Sacred Values of the World’s Religions: A Multidisciplinary Perspective - Sassi, Komarudin; Azzahra, Haramain (Peminat Ilmu Ushuluddin, 2023)
Abstract: This article discusses knowledge that focuses on comparative studies regarding the complexity of the sacred values of world religions from a multidisciplinary perspective. The tendency of previous research to review the sacred values of religions is limited to a monodisciplinary perspective, and they focused only on the field of spirituality as well as it was personal in nature. In fact, the view of the sacred value of religion as something spiritual has a broad spectrum, and it is also influenced by the environment, culture, and social interactions. The research method employs Rudolf Bultmann’s theological hermeneutical approach to the demythologizing framework. Through this theological hermeneutic, researchers comprehensively interpret the sacred values of religions into the socio-cultural aspects of contemporary humans. This research discovers that the sacred values of world religions are complex-dynamic, not partial-static, and play an important role in various aspects of life throughout the world. At the same time, this is an ideal time to make good use of the practice of sacred values of religions as an important source of community-based values from various parts of the world to develop an important bridge towards the “baldatun ṭayyibatun wa Rabbun Ghafūr society.”Keywords: Comparative Studies; Sacred Values; World Religions; Multidisciplinary Perspective.Abstrak: Artikel ini memperluas pengetahuan yang berfokus pada studi komparasi tentang kompleksitas nilai suci agama-agama dunia dalam perspektif multidisiplin. Penelitian sebelumnya cenderung meninjau nilai suci agama-agama sebatas perspektif monodisiplin dan tertuju hanya pada bidang spiritualitas dan bersifat personal. Padahal pandangan tentang nilai suci agama sebagai sesuatu yang spiritual memiliki spektrum yang luas dan juga dipengaruhi lingkungan, budaya, dan interaksi sosial. Metode penelitian menggunakan pendekatan hermeneutika teologis Rudolf Bultmann pada kerangka demitologisasi. Melalui hermeneutika teologis ini peneliti menginterpretasikan nilai suci agama-agama secara komprehensif ke dalam aspek sosial-budaya manusia kontemporer. Hasil penelitian ini menemukan bahwa nilai suci agama-agama dunia bersifat kompleks-dinamis bukan parsial-statis, dan memainkan peran penting dalam berbagai aspek kehidupan di seluruh dunia, sekaligus era kontemporer ini saat yang ideal untuk kembali memanfaatkan dengan baik praktik nilai suci agama-agama sebagai sumber penting nilai-nilai komunitarian dari berbagai belahan dunia guna membangun jembatan penting menuju masyarakat yang “baldatun thayyibatun wa Rabbun Ghafūr.”Kata Kunci: Studi Komparasi; Nilai Suci; Agama-agama Dunia; Perspektif Multidisiplin.